Clinical course and role of embolization in patients with spontaneous rupture of hepatocellular carcinoma - Park, Juil; Jeong, Yun Soo; Suh, Yun Seok; Kim, Hyo-Cheol; Chung, Jin Wook; Choi, Jin Woo (Frontiers in Oncology, 2022)
Background: A diverse clinical course after the spontaneous rupture of hepatocellular carcinoma (HCC) renders nonstandardized treatment protocols. Purpose: To evaluate clinical course and role of transcatheter arterial embolization (TAE) in patients with rupture of HCC. Materials and Methods: This retrospective study included 127 patients who were treated for ruptured HCC at single institution between 2005 and 2014. After multidisciplinary discussion, patients underwent medical management, TAE, emergency surgery or staged surgery. Patients were retrospectively divided into two groups based on the intent of treatment: curative and palliative. The rebleeding rate and 1-month and overall survival (OS) were compared between two groups. The incidence and survival of patients with intraperitoneal drop metastasis (IPDM) were also analyzed. Results: The overall rebleeding rate in patients who underwent TAE was 3.1% (3/96). One-month mortality rate was 6.3% (8/127). The rebleeding and 1-month mortality rates were not significantly different between two groups. OS was significantly higher in the curative treatment group (median: 12.0 vs 2.2 months, p<0.001). Among 96 patients who initially received TAE, ten patients underwent staged operation (10.4%). The median OS for medical management, TAE, emergency surgery and staged surgery was 2.8, 8.7, 19.1 and 71.1 months, respectively. Of all patients, 15.2% developed IPDM mostly within 1 year and their survival was poorer than that of patients without IPDM (median: 6.3 vs. 15.1 months, p<0.001). Conclusion: TAE provided effective immediate hemostasis with a low rebleeding rate and may serve as a bridge to elective surgery. IPDM frequently occurred within 1 year and manifested poor survival; thus, close surveillance should be considered for patients with spontaneous rupture of HCC.